Generation of formaldehyde and formaldehyde-d2 for hydroxymethylations and hydroxydeuteromethylations of difluoroenolates and difluorobenzyl carbanions. Issue 36 (13th April 2022) - Khatri, Hari R.; Han, Changho; Alkhodier, Reem A.; Adam, Amna T.; Islam, Baharul; Colby, David A.
Abstract : A method for the in situ production of formaldehyde from dimethylsulfoxide, bromine, and cesium carbonate is reported for reactions with difluoroenolates and difluorobenzyl carbanions. Abstract : A method for the in situ production of formaldehyde from dimethylsulfoxide, bromine, and cesium carbonate is reported for reactions with difluoroenolates and difluorobenzyl carbanions. This process also generates formaldehyde-d2 for the production of 2, 2-difluoro-1, 1-deuteroethanols. Mechanistic and computational studies further characterize the production of hydroxymethylated and hydroxydeuteromethylated difluorinated organic molecules.